Konsep Negara Kesejahteraan dari Waktu ke Waktu - MURYANTO AMIN (Politeia: Jurnal Ilmu Politik, 2011)
The concept of the welfare state is a concept that is still being debated. The debate is the events of the past and present. This study discusses the debate. This study found, in the debate, there are four meanings of the welfare state concept: First, the concept of the welfare state understood as the power of the state addressed to the national welfare; Second, the concept of the wel-fare state understood as undercover state collectivism by directing spending; Third, the concept of the welfare state understood as the beginning phase of the political absolutism; Fourth, the concept of the welfare state understood as a way to pay attention condition of the people who are not rich (poor). This debate can not be separated from the pull of the ideology social-ism and capitalism. The implication is that the welfare state can be called a middle way.Keywords: Welfare state, laissez faire, empirical libertarian.